366 Genomic profile of clear cell ovarian cancers and evolution with disease progression. (13th November 2020) - Mesnage, S; Robb, T; Blenkiron, C; Payne, K; Hameed, H; Shields, P; Houseman, P; Findlay, M; Chrystal, K; Stephens, R; Print, C; Wilson, M
Abstract : Introduction: In clear cell ovarian cancers (CCOC) limited data is available on genomic evolution with disease progression. Methods: 23 FFPE tumours collected from 12 patients with advanced CCOC, and 1 mixed clear cell endometrioid OC, treated at Auckland Hospital from 2003–2017, underwent whole exome sequencing (Macrogen), with matched normal tissue. Results: 8 patients had diagnostic samples, 5 had diagnostic and first relapse samples, of these 2 had samples from a second relapse. 10/13 patients had 10 distinct ARID1A mutations, most were indels. In 3 patients ARID1A mutations were present at diagnosis and relapse, in 1 patient ARID1A mutation was present at first and second relapse but absent at diagnosis. Other driver mutations were identified in PIK3CA 2/13, AKT1 2/13, PTEN 1/13, NOTCH1 1/13, SMARCA4 1/13, PPP2R1A 1/13, TP53 1/13 and ARID5B 1/13. Putative driver mutations in ACVR1B and IGF2R were seen in relapse and not diagnostic samples. Three patients had euploid tumours, the remainder had a range of aneuploidy, predominantly in chromosomes 8, 9, 16 and 19. Ploidy remained stable with relapse, except in one chemotherapy-naïve patient, who was euploid at diagnosis, and developed loss of heterozygosity (LOH) in several chromosomes at relapse. Tumour mutational burden (TMB) ranged from <1 to >10 mutations per MB, with no clear trend with disease progression. In one patient TMB was higher in the primary compared with 2 metachronous metastatic sites. Conclusion: There was little change in genomic characteristics with disease progression. One chemotherapy naïve patient developed LOH and increased TMB at relapse.